Intrinsic activity temporal structure reactivity to behavioural state change is correlated with depressive symptoms. (28th June 2020) - Duncan, Niall W.; Hsu, Tzu‐Yu; Cheng, Paul Z.; Wang, Hsin‐Yi; Lee, Hsin‐Chien; Lane, Timothy J.
Abstract: The brain's intrinsic activity plays a fundamental role in its function. In normal conditions this activity is responsive to behavioural context, changing as an individual switches between directed tasks and task‐free conditions. A key feature of such changes is the movement of the brain between corresponding critical and sub‐critical states, with these dynamics supporting efficient cognitive processing. Breakdowns in processing efficiency can occur, however, in brain disorders such as depression. It was therefore hypothesised that depressive symptoms would be related to reduced intrinsic activity responsiveness to changes in behavioural state. This was tested in a mixed group of major depressive disorder patients ( n = 26) and healthy participants ( n = 37) by measuring intrinsic EEG activity temporal structure, quantified with detrended fluctuation analysis (DFA), in eyes‐closed (EC) and eyes‐open task‐free states and contrasting between the conditions. The degree to which DFA values changed between the states was found to correlate negatively with depressive symptoms. DFA values did not differ between states in those with higher symptom levels, meaning that the brain remained in a less flexible sub‐critical condition. This sub‐critical condition in the EC state was further found to correlate with levels of maladaptive rumination. This may reflect a general cognitive inflexibility resulting from a lack in neural activity reactivity that may predispose people to overly engage in self‐directed attention. These results provide an initial link between intrinsic activity reactivity and psychological features found in psychiatric disorders. Abstract : Long‐range temporal correlations in EEG activity increase when the eyes are closed, compared to open. The amount that these change in the beta frequency band correlates with depressive symptoms, with a lack of change associated with more severe symptoms. Intrinsic activity in people with high depressive symptoms thus appears to respond less flexibly to changes in behavioural state. This reduced neural flexibility may be related to the cognitive inflexibility seen in depression.